Fludarabine, cyclophosphamide and lenalidomide in patients with relapsed/refractory chronic lymphocytic leukemia. A multicenter phase I–II GIMEMA trial. Issue 7 (3rd July 2017) - Mauro, Francesca R.; Carella, Angelo M.; Molica, Stefano; Paoloni, Francesca; Liberati, Anna M.; Zaja, Francesco; Belsito, Valeria; Cortellezzi, Agostino; Rizzi, Rita; Tosi, Patrizia; Spriano, Mauro; Ferretti, Antonietta; et al.
Abstract: The activity and safety of a regimen combining lenalidomide with fludarabine and cyclophosphamide (FC) was investigated in patients with relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL). Treatment consisted of six monthly courses of the FC regimen combined with 14 days of lenalidomide given at the starting dose of 2.5 mg during course 1. The maximum tolerated dose of lenalidomide was 5 mg. Forty patients were assessed for response, 66% were IGHV unmutated, 45% showed deletion 11q or 17p. The overall response and complete remission rates were 62.5% and 22.5%, respectively, the median progression-free and overall survival (OS) were 19 and 45 months, respectively. Grade 3–4 granulocytopenia was observed in 65% of cases, severe infections in 7.5%, the lenalidomide-related toxicity was mild. In conclusion, the results of this study demonstrate that low-dose lenalidomide associated with the FC schedule is an effective treatment for R/R patients with CLL, associated with an acceptable safety profile.